2012
DOI: 10.3109/10641963.2012.690474
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Postprandial Serum Levels of Gastrin in Normotensive and Hypertensive Adults

Abstract: Gastrin is a peptide hormone, which acts not only to regulate gastric acid secretion, but also to exert physiological actions such as the regulation of sodium balance. From a case (n = 95)-control (n = 82) study in Fuyang People's Hospital, Anhui Province, China, we found that the fasting serum gastrin levels are similar in normotensive and hypertensive adults but increased to higher levels in the latter group than in the former group after a mixed meal. We suggest that gastrin is involved in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Moreover, in hypertensive patients, fasting serum gastrin levels were inversely correlated with blood pressure, suggesting that gastrin is involved in the regulation of blood pressure 7, 32. Our laboratory found that the intrarenal infusion of gastrin induces natriuresis and diuresis 8.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, in hypertensive patients, fasting serum gastrin levels were inversely correlated with blood pressure, suggesting that gastrin is involved in the regulation of blood pressure 7, 32. Our laboratory found that the intrarenal infusion of gastrin induces natriuresis and diuresis 8.…”
Section: Discussionmentioning
confidence: 76%
“…Increased postprandial gastrin levels have been associated with a postprandial decrease of blood pressure in hypertensive patients 7. Moreover, in hypertensive patients, fasting serum gastrin levels were inversely correlated with blood pressure, suggesting that gastrin is involved in the regulation of blood pressure 7, 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrin is a peptide hormone, which regulates gastric acid secretion and exerts physiological actions such as the regulation of sodium balance (29). Gastrin has been suggested to be involved in blood pressure regulation, possibly via the regulation of sodium and water metabolism and/or the renin-angiotensin-aldosterone system (29).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin has been suggested to be involved in blood pressure regulation, possibly via the regulation of sodium and water metabolism and/or the renin-angiotensin-aldosterone system (29). Measurements of gastrin levels are taken primarily for the diagnosis of gastrin-producing tumors (gastrinomas), which cause Zollinger-Ellison syndrome.…”
Section: Discussionmentioning
confidence: 99%